2008
DOI: 10.3174/ajnr.a0964
|View full text |Cite
|
Sign up to set email alerts
|

3D Rotational Angiography: The New Gold Standard in the Detection of Additional Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE:During surgery of symptomatic aneurysms, additional small angiographic occult aneurysms are commonly found. With 3D rotational angiography (3DRA) small aneurysms are more easily depicted than with digital subtraction angiography (DSA). In this study we compare 3DRA with DSA in the depiction of small additional aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
141
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(152 citation statements)
references
References 11 publications
3
141
0
8
Order By: Relevance
“…Work-up of SAH with CTA versus conventional angiography is a frequently debated topic and, as pointed out by Kallmes et al, 8 CTA can result in false-negative results, and 3DRA probably remains the most accurate study in these patients. Van Rooij et al 9 have also reported that very small aneurysms can be commonly detected by 3DRA despite negative findings on DSA. These very small aneurysms can be interpreted as the loop of the vessel or can be overlapped by normal arteries in conventional DSA (Case 3), and 3DRA is useful in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Work-up of SAH with CTA versus conventional angiography is a frequently debated topic and, as pointed out by Kallmes et al, 8 CTA can result in false-negative results, and 3DRA probably remains the most accurate study in these patients. Van Rooij et al 9 have also reported that very small aneurysms can be commonly detected by 3DRA despite negative findings on DSA. These very small aneurysms can be interpreted as the loop of the vessel or can be overlapped by normal arteries in conventional DSA (Case 3), and 3DRA is useful in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some of these additional aneurysms may be surgically or endovascularly treated in the same or in a repeat procedure, but many will be left untreated because of small size, unfavorable aneurysm geometry, or location remote from the target aneurysm. Apart from this, patients with treated intracranial aneurysms are at risk for developing new aneurysms with time.…”
mentioning
confidence: 99%
“…In this procedure a small volume of brain tissue can be scanned, and aneurysms even of a size less than 3 mm can be depicted [95]. This technique allows a reconstruction of three-dimensional arteries and aneurysms and hence an approximate identification of the fluid and the solid parts in the scanned volume.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison study between CTA and DSA techniques is presented in [72], where DSA is found to be more accurate than CTA for reproducing the shape of a comparably large aneurysm and its relationship to the parent artery. In [95] it is shown that detection of much smaller aneurysms (even with a diameter less than 3 mm) is best performed on the basis of 3DRA. From a statistical point of view, in the clinical comparison study described in [96] 78% of the smaller aneurysms were missed using DSA compared to scans employing 3DRA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation